Smooth second-order sliding modes: Missile guidance application - Shtessel, Yuri B.; Shkolnikov, Ilya A.; Levant, Arie (Automatica (Oxford), 2007)
A new smooth second-order sliding mode control is proposed and proved using homogeneity-based technique for a system driven by sufficiently smooth uncertain disturbances. The main target application of this technique—the missile-interceptor guidance system against targets performing evasive maneuvers is considered. The smooth second-order sliding mode control-based guidance law is designed and compared with augmented proportional navigation guidance law via computer simulations of a guided missile intercepting a maneuvering ballistic target.